Progress in the knowledge of God according to St Thomas - Pérez de Laborda, Miguel (Acta Philosophica, 2009)
Thomas Aquinas sustains repeatedly that the essence of God is incomprehensible, though this thesis was never fully understood in all it’s radicalism since it appeared that it would prevent the development of a natural theology. This article shows that in Thomas’ opinion, by means of the “triple way”, (affirmation, denial, elevation) a rational knowledge of God is possible. This knowledge can progress, even if through all our efforts, the Essence of God still remains absolutely unknown.